A Latent Profile Analysis of Chinese Physicians' Workload Tethered to Paperwork During Outpatient Encounters - Li, Dehe; Hu, Yinhuan; Liu, Sha; Lu, Chuntao; Li, Jiayi; Zhou, Jinghan; Zhang, Yeyan; Lu, Shaoyu (Frontiers in Public Health, 2022)
Background: Physician dissatisfaction with more time spent on related paperwork but less time available for direct interaction with patients is increasing internationally. Increased physician workload resulting from paperwork might negatively affect their interaction with patients and increase the risk for burnout. This study aimed to investigate the level of physician workload tethered to paperwork during outpatient encounters and explore its latent workload subgroups among Chinese physicians. Methods: A cross-sectional survey was conducted via online questionnaire primarily in 24 hospitals in 6 provinces in Eastern, Central, and Western China from November 2020 to February 2021. The Chinese physician mental workload scale developed by our research team was used for workload assessment. Physicians were categorized into different subgroups of workload via latent profile analysis. Multinomial logistic regression was subsequently performed to examine how demographic variables differ among physicians belonging to different subgroups. Results: A total of 1934 valid questionnaires were received. Chinese physicians reported medium levels of workload while performing non-physician-patient communication work tasks characterized by paperwork during outpatient encounters. Four latent workload subgroups were identified: ‘low workload group’ (8.8%), ‘medium workload group’ (34.0%), ‘high workload group’ (42.1%) and ‘very high workload group’ (15.1%). Compared with the other latent workload subgroups, physicians belonging to the ‘very high workload group’ were more likely to be younger, married, those who had worse health status, lower educational levels and lower average monthly incomes, those who worked more years in the current institution, more hours per week and longer outpatient hours per week, and those who worked in public general hospitals, tertiary B hospitals and Obstetrics and Gynecology, and saw more than 50 outpatients per day, with more time spent on per patient. Conclusions: There exit four latent workload subgroups among Chinese physicians tethered to paperwork during outpatient encounters along with great individual variations among these subgroups. The characteristics of the latent “very high workload group” can help permit more targeted guidance for developing interventions with optimized human resource allocation to, in turn, increase the time available for direct interaction with patients, thereby resulting in improved quality of physician-patient interactions and decreased risk for physician burnout.